15-Deoxyspergualin in patients with refractory ANCA-associated systemic vasculitis: A Six-Month Open-Label Trial to Evaluate Safety and Efficacy - Birck, Rainer; Warnatz, Klaus; Lorenz, Hanns-Martin; Choi, Mira; Haubitz, Marion; Grünke, Mathias; Peter, Hans H.; Kalden, Joachim R.; Göbel, Ursula; Drexler, Johannes M.; Hotta, Osamu; Nowack, Rainer; et al. (Journal of the American Society of Nephrology, 2003)
ABSTRACT. The combination of cyclophosphamide (CYC) and oral corticosteroids is effective in the majority of patients with antineutrophil cytoplasmic antibody-associated vasculitis (AASV), but it carries substantial risk of drug-related morbidity and mortality. New regimens are desired, especially in refractory cases. The immunosuppressant 15-deoxyspergualin (DSG) is effective in experimental autoimmune disease and transplantation as well as in acute kidney transplant rejection in humans. To assess the efficacy and safety of DSG, an open label multicenter trial was conducted in patients with AASV who were either unresponsive or had contraindications for standard immunosuppressants. Included were 19 cases of Wegener granulomatosis and one case of microscopic polyangiitis. Nine of them had received CYC shortly before study entry without apparent therapeutic success. DSG (0.5 mg/kg per d) was given for 2 to 3 wk until the WBC count dropped to 3000/μl followed by a rest until at least a WBC of 4000/μl was reached again. This was repeated up to six cycles. During the study, no other immunosuppressants besides steroids were allowed. Disease improvement during treatment with DSG was achieved in 70% of cases (six cases of complete remission; eight cases of partial remission). Leucopenia occurred in each patient in a regular pattern during the cycles and was transient without exception. No mortality or septicemia was observed. Mild to moderate infections mainly in the respiratory tract were observed but resolved under adequate treatment without sequel. It is concluded that treatment with DSG is successful in patients with refractory Wegener granulomatosis under careful monitoring of WBC count. E-mail: rainer.birckmed5.ma.uni-heidelberg.de
Gesehen am 05.10.2022